New Approach in Treatment of Cancer & Viral Infection by Apis Mellifera L Venom Extracts (Honeybees Venom) - Ahmed Kamal, Samia (Journal of Skin Cancer Epidemiology, 2022)
Cancer cells need strong drug to be eliminated. Cancer lesions cure could achieve by topical application of crude bee venom. Bee venom medication used to prevent malignancies in groups most at risk (predisposing factors). Bee venom crosses the blood brain barriers because its components are very small. However, Bee venom contraindicated administered by intravenous injection because it’s hemolytic substance, mellitin which is powerful anticoagulant. However, the cationic peptides mellitin govern the mode of action of bee venom as anticancer and antiviral in vivo; 1 there is a negative charge on cancer cells, viral infected cells, diseased cells, and generally any cells that contain toxins or damage, and viruses are carrying negative charge even when it is outside the living body. 2Bee venom component (melittin) carries a positive charge, it destruct negatively charged cancer cells. 3 The role that the herpes virus is likely to play in increasing the severity of cancerous diseases, worsen the conditions: herpes viruses are opportunistic viruses that strike the body whose immunity is weakened for any reason. Therefore, the role of herpes virus must be neutralized when you planning to treat a cancer patient. Fortunately, bee venom is a powerful antiviral, and thus we hit three birds with one stone, that is, we kill cancer cells, kill opportunistic viruses, and improve tissue immunity to participate in the fight against cancer and get rid of toxic exudates more efficiently.
Keywords: Honeybees; mellitin; Bee venom; anticancer therapy; antivirals; cationic peptides; allergy management